Bhutan : Poverty Reduction Strategy Paper-Joint Staff Advisory Note. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The overarching objective of Bhutan's Tenth Five-Year Plan (10FYP)-which is also the Royal Government of Bhutan's Poverty Reduction Strategy Paper (PRSP)-is to sustain this trajectory and reduce poverty further. Political stability, prudent economic management, and development of the hydropower sector delivered robust economic growth during the 9FYP. Favorable economic performance was underpinned by sound macroeconomic policies. The 10FYP forecasts an average fiscal deficit of about 3 percent of GDP, the same as in the 9FYP and in line with the Royal Government of Bhutan (RGoB)'s strategic fiscal policy goals.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet